2011
DOI: 10.4196/kjpp.2011.15.2.83
|View full text |Cite
|
Sign up to set email alerts
|

HO-1 Induced by Cilostazol Protects Against TNF-α-associated Cytotoxicity via a PPAR-γ-dependent Pathway in Human Endothelial Cells

Abstract: A large body of evidence has indicated that induction of endogenous antioxidative proteins seems to be a reasonable strategy for delaying the progression of cell injury. In our previous study, cilostazol was found to increase the expression of the antioxidant enzyme heme oxygenase-1 (HO-1) in synovial cells. Thus, the present study was undertaken to examine whether cilostazol is able to counteract tumor necrosis factor-α (TNF-α )-induced cell death in endothelial cells via the induction of HO-1 expression. W e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…5A). Similarly, previous studies indicated that HO-1 induction was upregulated by PPARγ in human smooth muscle cells and vascular endothelial cells (34), and cilostazol, an inhibitor of phosphodiesterase type III, protected endothelial cells against tumor necrosis factor-α-induced cytotoxicity through HO-1 induction via a PPARγ-dependent pathway (43). …”
Section: Discussionsupporting
confidence: 53%
“…5A). Similarly, previous studies indicated that HO-1 induction was upregulated by PPARγ in human smooth muscle cells and vascular endothelial cells (34), and cilostazol, an inhibitor of phosphodiesterase type III, protected endothelial cells against tumor necrosis factor-α-induced cytotoxicity through HO-1 induction via a PPARγ-dependent pathway (43). …”
Section: Discussionsupporting
confidence: 53%
“…Hemeoxygenase-1 (HO-1) is an inducible form of the rate-limiting enzyme involved in heme catabolism. In preclinical models of tissue injury, HO-1 has been shown to confer cellular protection through inhibition of apoptosis, inflammation and cell proliferation [ 14 , 15 ]. To combat alcohol-induced liver damage, strategies to strengthen the protective effects of molecules, such as HO-1, and the development of new ways to reduce liver-damaging signals may be favorable treatment options.…”
Section: Introductionmentioning
confidence: 99%
“…According to previous literatures, heme oxygenase (HO)-1 was suggested as one of the down-stream effectors of PPARγ [11,13] . Our previous work showed that HO-1 could upregulate expression of p21 protein [10] which was considered as an inhibitor of cell proliferation.…”
Section: Introductionmentioning
confidence: 99%